Thermal cycling of YAG infiltration and plasma sprayed coatings as environmental barrier coating on ceramic heat shields for use in hydrogen operating gas turbines - Müller-Elmau, J.C.; Göbel, A.; Junge, P.; Müller, J.T.; Rousseau, T.C.; Görke, O.; Nikasch, C.; Kiliani, S. (Open ceramics, 2025)
Environmental barrier coatings (EBC) are intended to protect alumina ceramic tiles in hot water vapor conditions, enabling gas turbines to operate with higher hydrogen content or even pure hydrogen. For these operating conditions, yttrium aluminum garnet (YAG) promises the highest protection against hydrolysis, which can be applied via atmospheric plasmaspraying (APS). To enhance the protection efficiency, the coating is combined with a prior infiltration of the base material. The obtained design acts as in-depth protection even if the coating exhibits cracks. [Display omitted]